Galectin-9 in autoimmune hepatitis: Correlation between serum levels of galectin-9 and M2BPGi in patients with autoimmune hepatitis. Issue 35 (August 2019) - Matsuoka, Naoki; Kozuru, Hideko; Koga, Tomohiro; Abiru, Seigo; Yamasaki, Kazumi; Komori, Atsumasa; Fujita, Yuya; Tenmoku, Junpei; Asano, Tomoyuki; Sato, Shuzo; Suzuki, Eiji; Furuya, Makiko; et al.
Abstract : Abstract: Autoimmune hepatitis (AIH) is a disorder of unknown etiology in which immune-mediated liver damage progresses to cirrhosis or hepatocellular carcinoma (HCC). The mainstay therapy for AIH is steroids and other immunosuppressive treatments. Currently, there are no validated markers for monitoring immune-mediated hepatic inflammation. Galectin-9 has recently been identified as a potential biomarker in patients with chronic liver disease. The objective of this study was to determine whether Galectin-9 and other serum proteins are associated with active disease in AIH patients. We enrolled 77 Japanese patients with well-documented AIH who were identified from the National Hospital Organization-AIH-liver-network database, as well as 32 patients with chronic hepatitis C (CHC), 27 patients with SLE, and 17 healthy control subjects. Serum levels of galectin-9, and markers of liver injury were measured and compared between groups. Serum levels of galectin-9 were significantly higher in AIH patients than in CHC patients (13.8 ± 4.9 ng/mL vs 8.9 ± 3.0 ng/mL, P < .001) or healthy controls (13.8 ± 4.9 ng/mL vs 5.0 ± 1.3 ng/mL, P < .001). In AIH group, serum galectin-9 levels weakly correlated with alanine aminotransferase levels or total bilirubin (TB) and strongly correlated with C–X–C motif chemokine 10 (CXCL10) and Mac-2 binding protein glycosylation isomer (M2BPGi) levels, but did not correlate with the histological grade of liver fibrosis. Steroid treatment of AIH patients significantly reduced serum galectin-9 levels (14.1 ± 4.9 ng/mL vs 8.3 ± 3.8 ng/mL, P < .001). SLE patients exhibited higher galectin-9 levels, whereas the galectin-9 levels did not correlate with liver function tests such as alanine aminotransferase levels. Serum galectin-9 correlated with disease status in AIH patients and could thus be useful biomarkers to detect hepatic autoimmunity. Because circulating galectin-9 reflects autoimmune-mediated inflammation, it may have additional utility as a biomarker for other autoimmune disorders. Abstract : Supplemental Digital Content is available in the text